Speech and Language Disturbances in Neurology Practice - Oğuz Tanrıdağ (Türk Nöroloji Dergisi, 2009)
Despite the well-known facts discerned from interesting cases of speech and language disturbances over thousands of years, the scientific background and the limitless discussions for nearly 150 years, this field has been considered one of the least important subjects in neurological sciences. In this review, we first analyze the possible causes for this “stepchild” attitude towards this subject and we then summarize the practical aspects concerning speech and language disturbances. Our underlying expectation with this review is to explain the facts concerning those disturbances that might offer us opportunities to better understand the nervous system and the affected patients